Fire, herbivores, and vegetation type shape soil biochemistry in sodic patches of a semi-arid Savanna ecosystem - Malongweni, Siviwe Odwa; Van Tol, Johan (MDPI, 2022)
In the Kruger National Park (KNP), the lower slopes of catenas have open patches referred to as sodic patches. Fire and herbivores are dominant mediators of vegetation in sodic patches. The effect of fire and herbivores on soil properties of sodic patches remains largely understudied. Moreover, the co-existence of trees and grasses and how they influence savanna soils is an important but poorly understood phenomenon in ecology. Therefore, the present study aimed to determine the influence of 20 years of fire, herbivores, vegetation type, and their interaction on soil biochemistry of sodic patches on the Nkuhlu exclosures in the Kruger National Park, South Africa. We found a higher main effect of fire on available phosphorus, cation exchange capacity, and soil organic matter. The presence of herbivores caused an increase in soil exchangeable cations (K+, Ca2+, Na+, and Mg2+), organic matter, cation exchange capacity, and microbial activity. Tree canopies had a higher effect on total nitrogen, exchangeable Ca and Mg, soil organic matter, and cation exchange capacity than open grassland zones. Our results indicate that changes in vegetation structure due to fire and herbivores and their secondary impact on soil properties should be taken into consideration in managing savannas. Moreover, fire and herbivores play an important role in the maintenance of vegetation type (trees and grasses) in sodic patches.
Keywords: Canopy cover; Grassland zone; Grazing; Kruger National Park; Sodic zone; Soil properties; Tree canopy